2010
DOI: 10.4314/ajpherd.v16i1.53316
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a physical activity, diet and behaviour modification intervention on the self-perception of 9 to 12 year old overweight and obese children

Abstract: The aim of the study was to determine whether a physical activity, diet and behaviour modification intervention would significantly improve the self-perception of 9 to 12 year old overweight and obese children. A convenience sample of 38 subjects between the ages of 9 and 12 years (mean age = 11.0) participated in the study. Twenty children (N = 20), 13 girls and 7 boys, participated in the intervention programme for 13 week (3 times/week), while 18 children (N = 18), 11 girls and 7 boys, served as a control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Sahota et al (2001) reported a small increase in global self-worth for obese children but not children of healthy weight in the intervention schools, while a significant effect on psychosocial wellbeing was found in overweight first-grade children (Hartmann et al, 2010). These findings support previous research on overweight and sedentary children following separate after-school and hospital-based physical activity interventions (Kemp & Pienaar, 2010;Petty, Davis, Tkacz, Young-Hyman, & Waller, 2009). Previous research highlighted a negative relationship between overweight/obesity and aspects of a child's wellbeing such as self-perceptions of social acceptance and physical appearance (McCullough, Muldoon, & Dempster, 2009;Ottova, Erhart, Rajmil, Dettenborn-Betz, & Ravens-Sieberer, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Sahota et al (2001) reported a small increase in global self-worth for obese children but not children of healthy weight in the intervention schools, while a significant effect on psychosocial wellbeing was found in overweight first-grade children (Hartmann et al, 2010). These findings support previous research on overweight and sedentary children following separate after-school and hospital-based physical activity interventions (Kemp & Pienaar, 2010;Petty, Davis, Tkacz, Young-Hyman, & Waller, 2009). Previous research highlighted a negative relationship between overweight/obesity and aspects of a child's wellbeing such as self-perceptions of social acceptance and physical appearance (McCullough, Muldoon, & Dempster, 2009;Ottova, Erhart, Rajmil, Dettenborn-Betz, & Ravens-Sieberer, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…A non-significant decrease of 2.9 kg was also found in body weight. The self-perception of the group improved significantly as assessed by the Harter Scale (Kemp & Pienaar, 2010). The compliance to the programme decreased when the supervised part ended, again highlighting the need for professional supervision and sustained motivation of children in obesity treatment regimens.…”
Section: Applied Researchmentioning
confidence: 95%
“…In this regard obesity among children of different age groups and from different perspectives for a better understanding of the www.intechopen.com problem have been published. This i.a include the prevalence of childhood obesity in different age groups (Du Toit & Pienaar, 2003), relationship of childhood obesity with the motor (Du Toit & Pienaar, 2003); fitness, (Truter et al, 2010); psychological (Pienaar & Eggar, 2007;Kemp & Pienaar, 2010), physiological (Kemp & Pienaar, 2010) and academic abilities (Du Toit et al, 2011), as well as relationships of obesity with diagnosed motor delays such as Developmental Coordination Disorder among children .…”
Section: Applied Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Seabra et al(2013) and Fairclough et al (2012) furthermore studied the effect gender, weight and socio-economic status (SES) have on attitudes towards PA, and concluded that overweight and obese children tend to have lower perceptions of PA and also that boys and high SES children enjoy being physically active in comparison to girls, overweight and low SES children. Moreover, Kemp and Pienaar (2010) indicate that boys have higher athletic perceptions whereas girls have higher academic and behaviour perceptions, as well as that overweight and obese children's perceptions of athletics are lower when compared to their normal weight peers.…”
Section: Introductionmentioning
confidence: 99%